Effects of new and recycle flux on the mechanical properties of submerged arc welded (SAW) line pipe grade X52M and X65M / Meor Mohd Adli Taib - Meor Mohd Adli, Taib (2020)
Two line pipe grade X52M and X65M were manufactured using submerged arc welding process. For each grade, two different welding flux condition were simulated, i.e. 100% new flux and 100% recycle flux. The flux used was aluminate basic type trade name OP 132. The outside diameter and wall thickness for X52M was 610mm x 12.7mm and for X65M was 762mm x 14.3mm. Lower weld re-entrant angle and higher weld bead height were observed in recycle flux condition. Lower weld manganese content recorded in recycle flux condition. And lower mechanical tests (i.e. tensile, impact, and hardness) value reported for recycle flux condition. The mechanical properties reduced when welding condition changed from 100% new flux to 100% recycle flux.